Strategic management and mapping of corn farming for sustainable animal feed in Maros District, South Sulawesi, Indonesia - SULHAN MANAF; AZISAH AZISAH; EYMAL B. DEMMALLINO; SURYANI SYAMSUDDIN (Asian Journal of Agriculture, 2025)
Abstract. Manaf S, Azisah A, Demmallino EB, Syamsuddin S. 2025. Strategic management and mapping of corn farming for sustainable animal feed in Maros District, South Sulawesi, Indonesia. Asian J Agric 9: 542-553. The purpose of this study was to analyze corn mapping and internal and external factors that influence corn farming development strategies for the sustainability of animal feed in Tanralili Sub-district, Maros District, South Sulawesi, Indonesia. This study employed a range of data collection methods, including observation, social mapping, Focus Group Discussion, and interviews. The data analysis was ArcGIS and SWOT analysis, which was presented in qualitative descriptive form. The results of this study indicate that potential mapping based on the area of corn land in Tanralili Sub-district, Maros District, has a total area of 2,667.45 ha. The village with the most extensive corn land is Toddopulia Village, which has an area of 502.91 ha. Corn crop production in Tanralili Sub-district, Maros District, fluctuates every year, with a production value of 56.04 quintals/ha in 2021, 59 quintals/ha in 2022, and 53.17 quintals/ha in 2023. Internal and external factors of corn farming that have a significant influence are: (i) the existence of agricultural institutions (farmer groups), (ii) the use of agricultural technology is still lacking, (iii) government policy support, (iv) high market demand, (v) corn production centers, (vi) increasing feed needs and (vii) fluctuations in production prices. The corn farming business development strategy is in quadrant III, which is in a diversification position.